Artificial Intelligence in Political Communication: Philosophical and Theological Implications for Religious Values and European Integration Processes in Ukraine - Tselkovskyi, Gennadii (Journal for the study of religions and ideologies, 2026)
This study analyses the philosophical and theological challenges of using artificial intelligence (AI) in political communication, particularly in the context of the Russian-Ukrainian war and Ukraine's European integration processes. The phenomenon of disinformation, deepfake videos, and manipulative algorithms that undermine trust in the truth and threaten democratic culture is examined. The philosophical dimension shows that AI can limit free will, turn a person into an object of manipulation, and create conditions for an "epistemic crisis". In the theological context, the meaning of human dignity as the image of God and the values of freedom and truth, which should guide the public use of new technologies, are explored. Special attention is paid to the positions of the Ukrainian and European churches on the ethics of digital technologies, their role in shaping moral guidelines, and their partnership with the state. It is shown that the problem of AI for Ukraine is closely related to issues of national identity, opposition to Russian propaganda, and integration into the European humanitarian space. It is concluded that the effective use of AI is possible only under a human-centric approach, where technology serves man, and not vice versa, and where truth and freedom remain inviolable values.